Translanguaging as an Effective Approach for Implementing NEP 2020 - Rajeshwari, L. (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Languages are 'caught‘ not 'taught‘. A child learns to speak and communicate by merely observing the adults who talk around them. The key aspect of Fundamental Literacy is that the child must read with understanding and not mere reading as per NIPUN Bharat initiative towards achieving the NEP 2020 goal of FLN by 2025.In a diversified country like India where English is the common language spoken in the entire country, regional languages play an important role in the education system. As per NEP guidelines, education can be in the mother tongue up to the eighth grade along with two more languages. Children‘s thinking process is in their first language which they translate to the medium of their education for the purpose of evaluation. Adopting two languages in the print material and teaching process to enhance the critical thinking and problem-solving approach of the learner is the first step towards implementing three language systems.